A two-step decision making approach for identification of critical equipment using analytical hierarchy process and preference ranking organization method for enrichment evaluations with improved normalization - Khaira, Ashish (Array, 2019)
Generally, numbers of shops are present in large-scale industries. Therefore, it is necessary to identify critical equipment’s for ensuring lower failure rate. Multiple researchers’ applied risk based analysis to select critical equipment’s from one particular section of a plant; based on the feedback of industry personnel or of their own observations that increases the error probability. Apart from this, the decision making (DM) techniques usually provide the best alternatives, but in maintenance there is a need to identify critical or the worst performing equipment. Therefore, this research paper covers three parts: (1) a novel approach of two-step decision making for identifying critical section and then critical equipment in that section at an electrode graphite manufacturing plant; (2) an innovative methodology of normalization for the Analytic Hierarchy Process (AHP); (3) Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE) method for validation. This work identified "utility" section n this heavy industry as a critical section and "screw compressor number 5" as critical equipment. From maintenance point of view, “critical" refers to the worst performing ones. Therefore, if this research followed a conventional methodology, then some other section could randomly be considered as "critical" and the best performing equipment would get the 1st ranking. Apart from this, PROMETHEE also provided the same result which validates the methodology.